Xyloketal derivative C53N protects against mild traumatic brain injury in mice - Liang F; Su F; Wang X; Long S; Zheng Y; He X; Pang J; Pei Z (Dove Medical Press, 2018)
Fengyin Liang,1 Fengjuan Su,1 Xiaoxiao Wang,2 Simei Long,1 Yinglin Zheng,3 Xiaofei He,1 Jiyan Pang,3 Zhong Pei1 1Department of Neurology, Guangdong Provisional Key Laboratory for Diagnosis and Treatment of Major Neurological Diseases, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou 510080, People’s Republic of China; 2Department of Medical Oncology, Sun Yat-sen University Cancer Center, Guangzhou 510060, People’s Republic of China; 3School of Chemistry, Sun Yat-sen University, Guangzhou 510275, People’s Republic of China Purpose: Mild traumatic brain injury (mTBI), the most common type of TBI, can result in prolonged cognitive impairment, mood disorders, and behavioral problems. Reducing oxidative stress and inflammation can rescue the neurons from mTBI-induced cell death. Xyloketal B, a natural product from mangrove fungus, has shown good antioxidative and neuroprotective effects in several disease models. Here, we investigated the potential protection afforded by a xyloketal derivative, C53N, in a closed-skull mTBI model. Materials and methods: Skulls of mice were thinned to 20–30 µm thickness, following which they were subjected to a slight compression injury to induce mTBI. One hour after TBI, mice were intraperitoneally injected with C53N, which was solubilized in 0.5% dimethyl sulfoxide in saline. In vivo two-photon laser scanning microscopy was used to image cell death in injured parenchyma in each mouse over a 12-hour period (at 1, 3, 6, and 12 hours). Water content and oxidation index, together with pathological analysis of glial reactivity, were assessed at 24 hours to determine the effect of C53N on mTBI. Results: Cell death, oxidative stress, and glial reactivity increased in mTBI mice compared with sham-injured mice. Treatment with 40 or 100 mg/kg C53N 1 hour after mTBI significantly attenuated oxidative stress and glial reactivity and reduced parenchymal cell death at the acute phase after mTBI. Conclusion: The present study highlights the therapeutic potential of the xyloketal derivative C53N for pharmacological intervention in mTBI. Keywords: xyloketal derivative, mTBI, in vivo imaging, antioxidant activity, neuroprotective activity